PENGARUH BERBAGAI JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS BIMA - Henderikus Darwin Beja (Universitas Wahid Hasyim, 2020)
Shallots (Allium ascalonicum L) are a horticultural plant commodity that has high economic value and is widely consumed by humans as a mixture of cooking spices after chili. The purpose of this study was to determine the effect of spacing on the growth of bima variety (Allium ascalonicum L) and the best distance to increase the growth and yield of shallot (Allium ascalonicum L) bima varieties. The method used in this study was a randomized block design (RBD), with four replications and five treatments, namely, JT1: 15 cm × 15 cm, JT2: 20 cm × 10 cm, JT3: 20 cm × 15 cm, JT4: 20 cm. × 20 cm, HH5: 20 cm × 30 cm. The observation variables included plant height and number of leaves aged 4 mst and 6 mst, number of tubers per plant, tuber wet weight per plant, tuber wet weight per bed, and tuber dry weight per plant. The results of this study showed significant effect on the number of shallots aged 6 mst, the number of tubers per plant, tuber wet weight per plant, tuber dry weight per plant, and tuber wet weight per hectare. But not significantly different from the height of shallots aged 4 mst and 6 mst, and the number of shallots aged 4 mst and 20 cm x 20 cm (JT4) planting distance is the best planting distance in increasing the growth of 6 mst onion leaves (6 24.11 strands) and tuber wet weight per bed (1.92 kg / bed). Keywords: shallots, spacing, growth, yield